Population Dynamics of Bactrocera sp. Fruit Flies in Response to Methyl Eugenol Attractants on Various Types of Chili Peppers in Ambon City - John Alfred Patty (BIOSAINSTEK, 2026)
This study aims to obtain the types and morphological characteristics of fruit fly pests and compare the number of fruit fly populations trapped in various types of chili plants. This study used Methyl Eugenol with a dose of 1.5 ml / cc in three chili planting locations: Poka, Taeno and Kranjang. Observations of the population of fruit fly pests caught were carried out on the 3rd day after the trap was installed and repeated every 3 days until the 42nd day. Observations were carried out in the morning at 07.00 - 09.00 WIT. The results of the study showed that fruit flies found in chili plantations in Poka, Kranjang and Taeno villages, namely B. dorsalis and B. umbrosus were found in the three sample villages, while B. carambolae was only found in Taeno village. The highest population was in Taeno village 2,027 with an average of 289,57 individuals, then Kranjang village at 1,294 individuals with an average of 184, 86 individuals and the lowest in Poka village with a population of 852 individuals, with an average of 121,71 individuals.